Jus Mentimun (Cucumis sativus) dan Air Rebusan Daun Salam (Eugenia polyantha) menurunkan Tekanan Darah Wanita Pra Lansia - Anggraini, Melati; Maigoda, Tonny C; Pravitasari, Ayu (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2024)
The purpose of this study was to analyze the effect of giving cucumber juice and boiled bay leaf water on blood pressure in pre-elderly women in the work area of Telaga Dewa Health Center, Bengkulu City. The method used in this study was quasi- experimental with a random pre-test and post-test design. The treatment given to pre-elderly women (45-59 years) with blood pressure of 130/80-139/89 mm/Hg and not taking medication in the morning, namely 100 grams of cucumber juice and 100 grams of boiled bay leaf water, was given for 7 consecutive days. The analysis of the Wilcoxon test showed a significant relationship, namely P-value <0.005 for systolic blood pressure of 0.001 and diastolic blood pressure of 0.001. Cucumber juice and boiled bay leaf water can lower blood pressure in pre-elderly women. Cucumber juice and boiled bay leaf water can be used as the most functional agents recommended to help lower blood pressure. Tujualn penelitialn ini untuk menganalisis pengaruh pemberian pemberialn jus mentimun daln air rebusan daun salam terhadap tekanan darah wanita pra lansia di wilayah kerja Puskesmas Telaga Dewa Kota Bengkulu. Desalin yalng digunalkaln dallalm penelitialn ini aldallalh Quasi Experimentall dengaln ralncalngaln pre test alnd posttest design. Perlalkualn yalng diberikaln pada wanita pra lansia(45-59 tahun) dengan tekanan darah  130/80- 139/89 mm/Hg dan tidak sedang mengkonsumsi obat di pagi hari, yalitu jus mentimun 100 gram dan air rebusan daun salam sebalnyalk 100 gralm diberikaln selalmal 7 halri berturut-turut. Alnallisis daltal menggunalkaln uji Wilcoxon menujukaln aldal hubungaln yalng signifikaln yuitu P-vallue <0,005 untuk tekalnaln dalralh sistolik yalitu 0,001 daln sedalngkaln dialstolik 0,001. Jus mentimun daln air rebusan daun salam dalpalt menurunkan tekanan darah wanita pra lansia. Jus mentimun dan air rebusan daun salam dapat dijaldikaln sebalgali balhaln palngaln fungsionall yalng direkomendalsikaln untuk membalntu menurunkaln tekalnaln dalralh.